PENERAPAN HUKUMAN KEBIRI KIMIA (CHEMICAL CASTRATION) TERHADAP PELAKU TINDAK KEJAHATAN SEKSUAL PADA ANAK DI INDONESIA. - Siahaan, Ade Yuliany (BULETIN KONSTITUSI, 2022)
Sexual crime against children is a crime against humanity where the victim, who in this case is still a child, is hurt not only physically but also psychologically. The bad impact experienced by the victim is the same as destroying human values because this crime has robbed people of their rights to live safely and comfortably because they have received a bad stigma from the community so that not a few victims have lost their future. Based on this polemic, legal remedies must be enforced fairly against perpetrators of sexual crimes against children. The law must provide strict sanctions so as to provide a deterrent effect and be able to minimize the occurrence of sexual crimes against children in Indonesia. The application of chemical castration to perpetrators of sexual crimes against children is a new legal effort that is considered fair and firm in tackling these crimes. Although it is considered fair and firm, in the effort to apply the chemical castration law, there are still some problems because this is still relatively new and law enforcers in Indonesia are still not familiar with this legal remedy. The problems studied in this study are how to regulate chemical castration (Chemical Castration) based on applicable law in Indonesia and how the efforts of law enforcers in carrying out chemical castration executions in Indonesia. The research method used is a normative juridical approach and is expected to provide a comprehensive explanation of matters relating to the application of chemical castration to perpetrators of sexual crimes against children in Indonesia. Based on the results of this research study, the application of chemical castration to perpetrators of sexual crimes against children in Indonesia is basically regulated in Law Number 17 of 2016 concerning Child Protection and then for procedures for implementing chemical castration, installation of electronic detection devices, rehabilitation and announcement of the identity of the perpetrator. Sexual violence against children is regulated in PP No. 70 of 2020. Although the regulation of the application of chemical castration in Indonesia has been regulated, the efforts of law enforcers in carrying out the execution of castration punishment in Indonesia are still experiencing obstacles. Starting from the implementation process, which experienced pros and cons from various parties and the execution process that had not been clinically tested, which did not guarantee the effectiveness of the chemical castration punishment.